Hubungan Pola Asuh Ibu Dan Pengetahuan Ibu Tentang Stunting Dengan Kejadian Stunting Pada Anak Usia 12-24 Bulan Di Pandeglang, Banten Dan Tinjauan Menurut Pandangan Islam - Setyowati, Hany (Cerdika: Jurnal Ilmiah Indonesia, 2022)
WHO defines stunting as impaired growth and development in children due to chronic inadequate nutritional intake, recurrent infectious diseases and inadequate psychosocial stimulation. Children with developmental delays, especially at an early age, may experience delays in the development of other organs, including the brain. The type of research used in this study is quantitative research with the aim of examining the relationship between stunting and its risk factors in Pandeglang, Banten. So it can be concluded, if poor parenting affects the incidence of stunting in children. In Univariate research, it was found that male toddlers were more than women, but the difference between the two groups was not much different. In bivariate analysis, the results obtained in the mother’s group with poor knowledge were 74.1% of toddlers classified as stunted, while in the mother’s group with good knowledge only 2.4% of toddlers were classified as toddlers with stunting conditions.